A first principles study on the electronic origins of silver segregation at the Ag-Au (111) surface - Hoppe, Sandra; Müller, Stefan (Journal of applied physics, 2017)
The special electronic structure of gold gives rise to many interesting phenomena, such as its color. The surface segregation of the silver-gold system has been the subject of numerous experimental and theoretical studies, yielding conflicting results ranging from strong Ag surface enrichment to Au surface segregation. Via a combined approach of density functional theory (DFT) and statistical physics, we have analyzed the segregation at the Ag-Au (111) surface with different Ag bulk concentrations. Interestingly, we observe a moderate Au surface segregation, which is due to a charge transfer from the less electronegative Ag to Au. Canonical Monte Carlo simulations suggest that the calculated concentration profile with a Au-enriched surface layer remains stable up to higher temperatures. However, the presence of adsorbed oxygen reverses the segregation behavior and leads to strong Ag enrichment of the surface layer.